Din Lligwy Village
Roman influence extended to improvements in agriculture, iron smelting, and techniques of building. The introduction of the rectangular plan and the laying of coursed stonework appears here in imitation of Roman work. This particular village was enclosed by a pentagonal stone wall, but most settlements of the period were sited in indefensible positions, subservient to the occupying power.